2018
DOI: 10.3892/etm.2018.6262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential key genes associated with severe pneumonia using mRNA‑seq

Abstract: This study aimed to identify the potential key genes associated with severe pneumonia using mRNA-seq. Nine peripheral blood samples from patients with severe pneumonia alone (SP group, n=3) and severe pneumonia accompanied with chronic obstructive pulmonary disease (COPD; CSP group, n=3), as well as volunteers without pneumonia (control group, n=3) underwent mRNA-seq. Based on the sequencing data, differentially expressed genes (DEGs) were identified by Limma package. Following the pathway enrichment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In blood, genes enriched in aminoacyl-tRNA biosynthesis were negatively modulated in the 30-day death group versus the surviving group, which was similar to the observation that genes related to aminoacyl-tRNA biosynthesis such as TRNS1 and TRNM were downregulated in patients with severe pneumonia in comparison with healthy individuals. 57 Besides, genes related to mitochondrial functions were also downregulated in non-survivors in our study, including electron transport chain: OXPHOS system in mitochondria, energy coupled proton transmembrane transport against electrochemical gradient, and mitochondrial cytochrome c oxidase. Previous findings demonstrated that genes associated with oxidative phosphorylation such as electron transport chain complex I, IV and V were downregulated in blood of non-surviving patients with sepsis caused by CAP.…”
Section: Discussionsupporting
confidence: 54%
“…In blood, genes enriched in aminoacyl-tRNA biosynthesis were negatively modulated in the 30-day death group versus the surviving group, which was similar to the observation that genes related to aminoacyl-tRNA biosynthesis such as TRNS1 and TRNM were downregulated in patients with severe pneumonia in comparison with healthy individuals. 57 Besides, genes related to mitochondrial functions were also downregulated in non-survivors in our study, including electron transport chain: OXPHOS system in mitochondria, energy coupled proton transmembrane transport against electrochemical gradient, and mitochondrial cytochrome c oxidase. Previous findings demonstrated that genes associated with oxidative phosphorylation such as electron transport chain complex I, IV and V were downregulated in blood of non-surviving patients with sepsis caused by CAP.…”
Section: Discussionsupporting
confidence: 54%
“…There is a growing number of evidences demonstrated that aberrant gene expression, microRNA post-transcriptional regulation and DNA methylation played significant role in leukemogenesis (74)(75)(76)(77). Our study further discussed how overexpression of ANP32A affected prognosis from these three aspects.…”
Section: Discussionmentioning
confidence: 54%
“…With the high prevalence of neural networks and Deep Learning-based algorithms in the Computational Biology, it is clear that the advantages of optimization in a highly non-linear space are welcomed improvements in biomedicine [1][2][3][4][5][6][7]. In Bioinformatics, significant effort has been committed to harnessing transcriptomic data for multiple analyses [7][8][9][10][11][12][13] especially cancer survival prognosis [14,15]. Faraggi and Simon [16] was the first study to use clinical information to predict prostate cancer survival through an artificial neural network model.…”
Section: Introductionmentioning
confidence: 99%